Full text in PDF of the EDUCARE Journal, issue of February 2012 - EDUCARE, Editor Journal (EDUCARE, 2012)
This journal was firstly published on August 17, 2008 by Association of Indonesian Scholars of History Education (ASPENSI) in Bandung, West Java, Indonesia in collaboration â for the period of 2008 to 2011 and 2011 to 2013 â with Muhammadiyah University of Purwokerto (UMP) in Central Java, Indonesia. This journal is published twice a year i.e. August and February.Â